How “Modern” was Russian Imperialism? - Morrison, Alexander Stephen (My University, 2012)
In this paper I explore the characteristics which historians normally attribute to 'modern' forms of Imperialism, and whether these make sense when applied to Russia. I conclude by making some tentative suggestions as to where the real distinctiveness of the Russian Empire lies.
Keywords: Imperial History; Colonialism; Russian History; Empire; Imperialism